1992
DOI: 10.1128/jcm.30.1.243-244.1992
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus intermedius, Streptococcus constellatus, and Streptococcus anginosus (the Streptococcus milleri group): association with different body sites and clinical infections

Abstract: The associations of Streptococcus intermedius, S. constellatus, and S. anginosus (the three species of the S. mileri group) with clinical infections and sites of isolation were investigated by using a simple biochemical scheme to identify a collection of 153 clinical isolates. S. intermedius was associated with abscesses of the brain and liver, while both S. anginosus and S. constellatus were isolated from a wider range of sites and infections. S. anginosus strains predominated in both genitourinary and gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
195
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(201 citation statements)
references
References 13 publications
3
195
0
3
Order By: Relevance
“…From the available data, it cannot be determined whether this species played a causal role in the subject's clinical disease or whether the species survived the series of treatments that some of the subjects had hud prior to entry into the study. S. eonstelhitus has been implicated in other oral and extra-oral infections (Shinzalo&Saito 1994, Whiley et al 1992, Levin et al 1982. It is worth noting that the taxonomic position of S. eoustellatus has been investigated for some time because of its similarity to strains of S. intermedius and S. anginosus.…”
Section: Discussionmentioning
confidence: 99%
“…From the available data, it cannot be determined whether this species played a causal role in the subject's clinical disease or whether the species survived the series of treatments that some of the subjects had hud prior to entry into the study. S. eonstelhitus has been implicated in other oral and extra-oral infections (Shinzalo&Saito 1994, Whiley et al 1992, Levin et al 1982. It is worth noting that the taxonomic position of S. eoustellatus has been investigated for some time because of its similarity to strains of S. intermedius and S. anginosus.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, among the group, the pathogenicity of each species seems to be different. Whiley et al [5] reported that Streptococcus intermedius was associated with abscesses of the brain and liver, while Streptococcus anginosus and Streptococcus constellatus (S. constellatus subsp. constellatus) were isolated from a wider range of sites and infections.…”
Section: Introductionmentioning
confidence: 99%
“…It is often associated with pyogenic infections, including endocarditis. [7][8][9] S. anginosus DNA has also been found in head and neck squamous cell carcinomas 10) ; it was found much less frequently in non-cancerous tissues of the esophagus and was absent from the colon, lung, bladder, renal, and cervical cancer tissues. 6) Therefore, it was suggested that S. anginosus DNA is associated with cancers in the upper digestive tract, although the involvement of S. anginosus infection in the carcinogenic process has not been clarified.…”
mentioning
confidence: 99%